Isolation and characterization of exopectinase from Bacillus licheniformis FMB9 isolated from agricultural soil - Alqahtani, Fatimah; Aly, Magda; Bokhari, Fardos; El-Nogoumy, Baher Ali; Alshehri, Wafa (Journal of Contemporary Medical Sciences, 2021)
Objectives: This study aimed to isolate and identify potential pectinase producing bacterium as well as optimization of its various parameters for maximum enzyme production. Methods: A total of forty-three bacterial isolates were obtained from agriculture soil in Jeddah city using standard plate count method. Primary screening was done by hydrolysis of pectin on agar plate and measuring the clear zone after adding iodine-potassium iodide solution. Pectinase activity was determined by measuring the increase in reducing sugar formed by the enzymatic hydrolysis of pectin. Results: Among the bacterial isolates, the isolate FMB9 exhibited higher pectinase activity in broth medium and was selected for further studies. The selected bacterial isolate FMB9 was identified as Bacillus licheniformis FMB9 with similarity level 97% to B. licheniformis AS10. The isolate was found to produce maximum pectinase at 37Â°C with pH 7 upon incubation for 72 hours, while cultured in production medium containing citrus pectin and yeast extract as carbon and nitrogen sources, respectively. The enzyme was purified using column chromatography and was characterized. It showed maximum activity at 45â—¦C. Bacillus licheniformis pictinase was affected by pH values and optimum activity was at pH 5. The molecular weight was also determined and compared with other pectinases. Conclusion: Pectinase produced from bacteria can be purified and used in many technological applications in food and medicine.